Stigma of Sickle Cell Disease: A Systematic Review. (3rd August 2018) - Bulgin, Dominique; Tanabe, Paula; Jenerette, Coretta
Abstract: The aim of this systematic review was to synthesize the literature regarding health-related stigma in adolescents and adults living with sickle cell disease (SCD). Four domains were identified from 27 studies: (1) social consequences of stigma; (2) the effect of stigma on psychological well-being; (3) the effect of stigma on physiological well-being; and (4) the impact of stigma on patient-provider relationships and care-seeking behaviors. Current literature revealed that SCD stigma has detrimental consequences. Methodological issues as well as research and practice implications were identified. Future research should further examine the impact of health-related stigma on self-management of SCD.